Technique proposal and application for risk assessment in collective basic sanitation system in rural areas - Bezerra, Nolan Ribeiro; Baracho, Rafaella Oliveira; Oliveira, Thaynara Lorrayne de; Scalize, Paulo Sérgio (Electronic Journal "Fórum Ambiental da Alta Paulista", 2022)
Nowadays, apply risk assessment processes, from health perspective in all basic sanitation components (water supply, sanitary sewage, solid waste and rainwater management), in order to follow the Resolution 64/292 it is a reality. In this context, this article aimed to propose a risk assessment process (RAP) for collective basic sanitation structures and apply it on a riverside community in Goiás state of Brazil. The steps used included scope definition, technique selection for risk assessment and RAP approach and application. The community studied was Arraial da Ponte, which has collective systems for water supply, solid waste and rainwater management. The selected technique was the probability/consequence matrix, according to the criteria established in NBR IEC/ISO 31010:2021 and proposal included identification stages of RAP risk factors, hazards, contamination route and hazardous events, as well as characterization and risk prioritization. It was based on the components of risk management process of NBR ISO 31000 and on World Health Organization recommendations described for water and sanitary sewage safety plan manuals. As result, health risks were identified in all basic sanitation components, with levels ranging from moderate to unacceptable. The risks showed need for greater attention from managers, as effective public policies implementation. Finally, the RAP managed to prioritize hazardous events and their associated risks, being able to help in the construction of plans and investments in the evaluated community.